The Nexus between Antidumping Petitions and Exports during the Global Financial Crisis: Evidence on the People's Republic of China - Faqin Lin; Hsiao Chink Tang; Lin Wang (Asian Development Bank (ADB), 2014)
This paper quantifies how the People's Republic of China's (PRC) export volume to its major trading partners during the global financial crisis affects the antidumping (AD) petitions filed by the trading partners against the PRC. Focusing on the AD petitions at the Harmonized System (HS) Code 8-digit level and the PRC's exports at the HS 2-digit level, we construct three instrument variables at the same HS level for export volume. These instruments—documents required, time taken, and container charges incurred for goods traded across borders—represent trade costs obtained from the World Bank's Doing Business Project. We find rising exports from the PRC lead to rising AD petitions against the country. Instrumental variable estimates indicate that a 1 percentage point rise in the PRC's export volume raises the number of AD petitions against the country by about 0.3 percentage point, and the probability of receiving AD petitions by 3.6 %. These estimates are about 10 times larger than those found in ordinary least square regressions. Their quantitative significance underlines why it is important to consider the issue of export endogeneity in the estimation. Moreover, it highlights the failure of the current trade statistics to account for the true value-added of traded goods, and how this has particularly disadvantaged the PRC, given its position as the factory of the world.
hdl:11540/2564
Keywords: F13; F14; F59; 330; International trade; antidumping; instrument variable; People's Republic of China